The Use of Makassar Malay Dialect in Food Buying and Selling Interactions on Instagram Social Media - Andi Samsu Rijal; Suhandano Suhandano; Hayatul Cholsy (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The Makassar Malay dialect is a variation of Indonesian Langauge. The use of the Makassar Malay Dialect arose because of the contact of languages both in orality and also in social media. This dialect was found in situations of buying and selling food interactions through Instagram social media. This article aimed to described the characteristics of the use of the Makassar Malay Dialect and the factors of the use of code mixing the Indonesian Makassar Malay Dialect with other codes in the interaction of buying and selling food through Instagram social media carried out by netizens in Makassar City. The data of this qualitative research focused on speech interactions in of buying and selling food through Instagram social media. This speech was contained in the comments column for uploading food advertisements to culinary Instagram accounts. There were various language codes used by participants such as the Indonesian language with the Makassar Malay dialect, regional and foreign language codes. The use of Makassar Malay dialect was in the form of words and affixes. The use of these dialects was in the form of code mixing, namely internal code mixing and outer code mixing. The use of the Makassar Malay dialect because of language contact and as the result of language adaptation.